On the nitroxide mediated polymerization of methacrylates derived from bio-sourced terpenes in miniemulsion, a step towards sustainable products. Issue 6 (23rd December 2019) - Noppalit, Sayrung; Simula, Alexandre; Billon, Laurent; Asua, José M.
Abstract : The typical use of toxic solvents, expensive control agents and the need of intermediate purification steps hinders the introduction of bio-sourced monomers into industrially viable block copolymers. This study aims at overcoming these limitations. Abstract : The incorporation of monomers derived from natural resources into industrially viable block copolymers is a long-standing problem that has not been appropriately solved yet due to a combination of issues that include the use of toxic solvents, relatively expensive control agents, and the need of intermediate purification steps. This study aims at overcoming these limitations. Nitroxide mediated polymerization of methacrylates synthesized from bio-resourced terpenes is carried out in miniemulsion using Dispolreg 007, an alkoxyamine that is produced through a cost effective and easily scalable synthetic route. Well-defined poly(tetrahydrogeraniol methacrylate)- b -poly(cyclademol methacrylate) diblock copolymers are obtained at high monomer conversions (>90%), without the need for intermediate purification steps. The resulting "soft"/"hard" diblock copolymers show good potential as waterborne pressure-sensitive adhesives.